Circulating T cell status and molecular imaging may predict clinical benefit of neoadjuvant PD-1 blockade in oral cancer - Tanja D de Gruijl; Rieneke van de Ven; K Hakki Karagozoglu; Pim de Graaf; Ronald Boellaard; Ruud H Brakenhoff; C René Leemans; Gerben J C Zwezerijnen; C Willemien Menke-van der Houven van Oordt; Iris H C Miedema; Niels E Wondergem; Jan-Jaap Hendrickx; et al. (Journal for ImmunoTherapy of Cancer)
Background Addition of neoadjuvant immune checkpoint inhibition to standard-of-care interventions for locally advanced oral cancer could improve clinical outcome.Methods In this study, 16 evaluable patients with stage III/IV oral cancer were treated with one dose of 480 mg nivolumab 3 weeks prior to surgery. Primary objectives were safety, feasibility, and suitability of programmed death receptor ligand-1 positron emission tomography (PD-L1 PET) as a biomarker for response. Imaging included 18F-BMS-986192 (PD-L1) PET and 18F-fluorodeoxyglucose (FDG) PET before and after nivolumab treatment. Secondary objectives included clinical and pathological response, and immune profiling of peripheral blood mononuclear cells (PBMCs) for response prediction. Baseline tumor biopsies and postnivolumab resection specimens were evaluated by histopathology.Results Grade III or higher adverse events were not observed and treatment was not delayed in relation to nivolumab administration and other study procedures. Six patients (38%) had a pathological response, of whom three (19%) had a major (≥90%) pathological response (MPR). Tumor PD-L1 PET uptake (quantified using standard uptake value) was not statistically different in patients with or without MPR (median 5.3 vs 3.4). All major responders showed a significantly postnivolumab decreased signal on FDG PET. PBMC immune phenotyping showed higher levels of CD8+ T cell activation in MPR patients, evidenced by higher baseline expression levels of PD-1, TIGIT, IFNγ and lower levels of PD-L1.Conclusion Together these data support that neoadjuvant treatment of advanced-stage oral cancers with nivolumab was safe and induced an MPR in a promising 19% of patients. Response was associated with decreased FDG PET uptake as well as activation status of peripheral T cell populations.